Audience Acceptance of the Ethics of Hijab-Wearing Women in Oklin Fia’s Social Media Content - Yasinta Nur Laila Shafa; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2024)
This study aims to explore audience reception regarding the ethical implications of a hijab-wearing woman's content on social media, focusing on Oklin Fia's controversial videos, particularly one where she provocatively licks an ice cream cone. Utilizing a qualitative approach with Stuart Hall's encoding/decoding theory, the research findings reveal diverse interpretations among audiences regarding the ethical conduct of hijab-wearing women in Oklin Fia's content. Non-Muslim informants positioned themselves in opposition to the ice cream-licking video, perceiving the hijab as a symbol of Islamic identity.